Very High Dehydroepiandrosterone Sulfate (DHEAS) in Serum of an Overweight Female Adolescent Without a Tumor - Iliev, Daniel I.; Braun, Regina; Sánchez-Guijo, Alberto; Hartmann, Michaela; Wudy, Stefan A.; Heckmann, Doreen; Bruchelt, Gernot; Rösner, Anika; Grosser, Gary; Geyer, Joachim; Binder, Gerhard (Frontiers in Endocrinology, 2020)
Introduction: An increase of serum DHEAS is observed in premature adrenarche and congenital adrenal hyperplasia. Very high DHEAS levels are typical for adrenal tumors. Approximately 74% of DHEAS is hydrolyzed to DHEA by the steroid sulfatase (STS). The reverse reaction is DHEA sulfation. Besides these two enzyme reactions the DHEAS transport through the cell membrane is important for its distribution and excretion. Case Presentation: We present a female adolescent with overweight and a very high DHEAS. The presence of a DHEAS-producing tumor was rejected using ultrasonography, MRT and dexamethasone suppression. STS deficiency was suspected. Sequence analysis revealed a heterozygous nonsense mutation which predicts a truncation of the carboxyl region of the STS that is implicated in substrate binding. No partial gene deletion outside exon 5 was detected by multiplex ligation-dependent probe amplification. The bioassay revealed normal enzyme activity in patient’s leukocytes. A defect of transporter proteins was suggested. Both efflux (MRP2 and BCRP) and uptake (OATP and OAT carriers) transporters were studied. Sequence analysis of exons revealed a heterozygous Q141K variant for BCRP. Conclusions: A novel heterozygous nonsense mutation in the STS gene and a known heterozygous missense variant in the BCRP gene were found. The heterozygous nonsense mutation in the STS gene is not supposed to be responsible for STS deficiency. The BCRP variant is associated with reduced efflux transport activity only in its homozygous state. The combination of the two heterozygous mutations could possibly explain the observed high levels of DHEAS and other sulfated steroids.